GAMBARAN HISTOLOGIS RAMBUT PENDEK PADA ANJING MUDA DAN TUA - , KARTIKA KUSUMA WATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Dog (Canis familiaris) based on its hair can be classified into two groups, short and long hair. Hair commonly indicates the clinical health of a dog. Histologically, hair from outer to inner as structured, the cuticle for protection, the cortex as pigmented shaft, and the medullar is concentric of the hair. The difference of hair structure between young and old dog can be seen from the hair structure for the reason to know the changes that caused by aging proccess. This study applies eighteen samples of short-haired dogs, consist of nine samples are elders (more than five years old) and nine samples are youngers (one to six months old) which are clinically health. The method of the study is by sampling at the dorsal of the dog, making histologic-hair preparat by Hematoksilin Eosin (HE) staining, and measuring hair thickness on each part of hair in three points of measurement on each sample. The result shows that cuticle, cortex, and medullar in short-haired old-dogs are thicker then the youngers. Yet, unfortunately it does not show significant result. The hair of old dogs have flatted cuticle, fastened cortex, and thick medullar with much cell vacuolization. In the other hand, the hair of young dogs have unflatted cuticle, unfastened cortex, and thin medullar without any cell vacuolization. Based on the study, we can draw a conclusion that histologically, the medulla of old dogs are thicker than the youngers. Vacuolization can be found at the medullar of old dogs hair.